Penyusunan dan Penerapan Laporan Keuangan bagi Usaha Mikro, Kecil, dan Menengah Berdasarkan Standart Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik (SAK ETAP) Pada UMKM Batik Arum Manis Kota Probolinggo - Riyanda Maghfiratun Hasanah; R. Hery Koeshardjono (Ecobuss, 2017)
This study aims to determine the application of SAK ETAP in the preparation of financial statements SMEs Arum Manis Batik in District Jati Mangunharjo Urban Village Probolinggi East Java. This type of research is action research. Based on the data result of the research, it is known that in UMKM Batik Arum Manis did not record the financial statement at all, the owner only keeps the evidence of the financial transaction in the form of sales note of batik and the purchase note of materials for batik. Data analysis techniques, which are used are data reduction, data presentation, and withdrawal of conclusions or verification. And reinforced by content analysis techniques with discourse method. The results of this study indicate that the UMKM Batik Arum Manis has not done the preparation and application of financial statements on its business, whereas according to the Financial Accounting Standards Entity Without Public Accountability (SAK ETAP) there are five types of financial statements that must be applied to each UMKM ie balance sheet, income statement, Statement of changes in equity, cash flow statement, and notes to the financial statements. Keywords: Financial Statement, SAK ETAP, UMKM.